ANALISIS KUALITAS UDARA LABORATORIUM TEKNIK SIPIL UNIVERSITAS ISLAM INDONESIA BERDASARKAN PARAMETER: TSP, PB, DAN CR TOTAL - Antari, Syifa Anisa; Wantoputri, Noviani Ima; Abidin, Azham Umar; Nugroho, Adam Rus (Universitas Pelita Bangsa, 2025)
The air quality in the Civil Engineering Laboratory is influenced by practical activities involving materials such as cement, concrete, asphalt, aggregates, and steel, all of which can generate Total Suspended Particulate (TSP) and heavy metals such as Lead (Pb) and Total Chromium (Cr). This study aims to analyze the differences in TSP, Pb, and Cr concentrations during periods with and without laboratory activities, as well as to identify risk perceptions and potential health impacts among laboratory users. Sampling was conducted in the Construction Materials Laboratory and the Highway Laboratory using a Low Volume Air Sampler (LVAS) for TSP and Atomic Absorption Spectrophotometry (AAS) for Pb and Cr analysis. Results show that TSP concentrations increased significantly during practical sessions, with the highest value of 2.888 mg/m³ recorded in the Highway Laboratory. The highest Pb concentration reached 0.065888 mg/m³, while Cr peaked at 0.0024 mg/m³, with several Cr measurements exceeding the threshold set by the Ministry of Manpower Regulation No. 5 of 2018. Questionnaire responses indicated exposure to dust, particulate deposits, metallic or chemical odors, and reported health complaints such as coughing, shortness of breath, skin irritation, and headaches. Although some parameters remained below regulatory limits, potential health risks persist due to cumulative exposure and inadequate ventilation.